Congenital Insensitivity to Pain: A Case Report and Review of the Literature - Leema Reddy Peddareddygari; Kinsi Oberoi; Raji P. Grewal (Case Reports in Neurological Medicine)
Congenital insensitivity to pain (CIP) is a rare autosomal recessive genetic disease caused by mutations in the SCN9A gene. We report a patient with the clinical features consistent with CIP in whom we detected a novel homozygous G2755T mutation in exon 15 of this gene. Routine electrophysiological studies are typically normal in patients with CIP. In our patient, these studies were abnormal and could represent the consequences of secondary complications of cervical and lumbosacral spine disease and associated severe Charcot’s joints.